Adult attachment insecurity is positively associated with medically unexplained chronic pain. (18th April 2017) - McWilliams, L.A.
Abstract: Background: Attachment insecurity (i.e. anxiety in relationships and/or discomfort in close relationships) is associated with self‐reports of physical symptoms, medically unexplained symptoms and health conditions involving pain. Medically unexplained chronic pain (MUCP) may represent a particularly severe form of symptom reporting that is also characteristic of individuals with insecure attachment. This study investigated relationships between adult attachment style ratings and past‐year MUCP in a sample of the general U.S. population and the ability of attachment style ratings to account for variance in past‐year MUCP beyond that accounted for by potential confounders. Method: Data from the National Comorbidity Survey Replication ( N  =   5645) were used. Attachment was assessed with an interview‐administered version of a commonly used self‐report measure of secure, anxious and avoidant attachment. MUCP was assessed with a brief interview. Depressive and anxiety disorders were included as covariates and were assessed with a fully structured interview based on DSM‐IV criteria. Results: The past‐year prevalence of MUCP was 2.45% (95% CI = 2.07–2.83). The two insecure attachment styles (i.e. anxious and avoidant) were positively associated with MUCP. These associations remained statistically significant after adjusting for demographic variables and depressive and anxiety disorders. When the two insecure attachment styles were considered together, only avoidant attachment remained significantly associated with MUCP. Conclusion: Attachment insecurity ratings were positively associated with past‐year MUCP and remained so after statistically adjusting for depressive and anxiety disorders. Further research aimed at understanding the mechanism(s) responsible for the association between attachment insecurity and MUCP is warranted. Significance: Consistent with earlier research regarding transient physical symptoms, medically unexplained chronic pain was associated with attachment insecurity. Understanding the mechanisms responsible for this association could guide treatment innovations.